Preparation, Molecular Structure and Morphological Studies of DBSA Doped (M-Toluidine-Co-2-Ethylaniline) Copolymer Composites for flexible Sensor Applications in Agricultural Field - Vijayanand , P S; Mahudeswaran , A; Vivekanandan , J; Ashokan , S (International Journal of Membrane Science and Technology, 2023)
A new series of dodecyl benzene sulphonic acid(DBSA) doped copolymer was synthesized using two different monomers m-toluidine and 2-ethylaniline with silver nanoparticles. The synthesized copolymer nanocomposite is soluble in Dimethylformamide (DMF), Tetrahydrofuran (THF), Dimethyl sulfoxide (DMSO), and N-Methylpyrrolidone (NMP). The synthesized polymer is analysed by various characterisation techniques. The absorption peaks around 316 and 598 nm confirm the presence of ? – ?* transition and n – ?* transition. The increase in the ethyl aniline ratio in the feed induced blue shift in the absorption peak. FTIR spectra confirms the presence of benzenoid and quinoid ring. The XRD pattern indicates the amorphous pattern of the polymer. SEM image revealed a large number of smooth surfaced particles agglomerate together. Ordered spherical sized growth of the particles with layered architectures, Nano sized tubular or nanotube growth along with porous structures was observed in the SEM image. The electroactive study of the composite confirms the semiconducting nature 1.04 × 10-6 to 2.86 × 10-8 S/cm, which can be used as basic materials for the manufacturing electric and electronic components in sensor field. The application of this electroactive materials are under taken for moisture sensor studies in the future for precision agriculture.